Don't trick me: An event-related potentials investigation of how price deception decreases consumer purchase intention. (20th November 2019) - Fu, Huijian; Ma, Haiying; Bian, Jun; Wang, Cuicui; Zhou, Jie; Ma, Qingguo
Highlights: Price deception played a negative role in purchase decision making when it was noticed by the participants. The truthful condition led to higher purchase rate and shorter reaction time. The N2 deflection was more negative in the deceptive (vs. truthful) condition. The LPP amplitude was larger in the truthful (vs. deceptive) condition. Abstract: As a kind of information deception, price deception is adopted by some online sellers as an approach to mislead the consumers into buying their products. However, when consumers have sufficient knowledge about the price information, the effect of price deception on their purchase decision making remains elusive. Therefore, behavioural and event-related potentials measures were combined to investigate this issue. Behaviourally, a higher purchase rate and reduced reaction time were observed in the truthful condition relative to the deceptive condition, suggesting that the truthful condition was more favourable to the participants. At the neural level, the truthful condition triggered an attenuated N2 and an increased LPP compared with the deceptive condition, indicating less cognitive and decisional conflict and more positive evaluation of the truthful condition. Taken together, these results revealed the negative impact of price deception on purchase decision making and its potential neural substrates.